1999
DOI: 10.1002/hep.510290633
|View full text |Cite
|
Sign up to set email alerts
|

Development of A New, Simple Rat Model of Early Alcohol–Induced Liver Injury Based on Sensitization of Kupffer Cells

Abstract: The continuous intragastric in vivo enteral feeding model in the rat developed by Tsukamoto and French has been very useful; however, it requires surgical expertise. Recently, we found that Kupffer cells isolated from rats treated only once with ethanol were sensitized to endotoxin 24 hours later. Accordingly, these experiments were designed to determine if a new, simple animal model of ethanol hepatotoxicity could be developed based on Kupffer cell sensitization. Female Wistar rats were given ethanol (5 g/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 34 publications
7
76
2
1
Order By: Relevance
“…The modulatory potential of acute alcohol on cytokine expression includes attenuation of TNF-␣ and augmentation of IL-10 production in monocytes (2,3,11). Ethanol generates oxidative stress, which plays an important role in immune cell activation as well as in alcoholic liver injury (14,35,36). HO-1 is an important antioxidant molecule and its up-regulation is a critical cytoprotective mechanism activated during cellular stress (8,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modulatory potential of acute alcohol on cytokine expression includes attenuation of TNF-␣ and augmentation of IL-10 production in monocytes (2,3,11). Ethanol generates oxidative stress, which plays an important role in immune cell activation as well as in alcoholic liver injury (14,35,36). HO-1 is an important antioxidant molecule and its up-regulation is a critical cytoprotective mechanism activated during cellular stress (8,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Despite convincing data indicating the cytoprotective function of HO-1 in oxidative stress, the mechanisms by which HO-1 serves as a cytoprotectant remain poorly understood. LPS, a potent HO-1 activator, has a central role in alcohol-induced liver damage via activation of Kupffer cells, the resident liver macrophages (14). LPS binds to CD14 and TLR4 at the cell surface (15) and then activates the MAPK pathways, including p38, p42/p44 ERK, and JNK (15)(16)(17).…”
mentioning
confidence: 99%
“…In �articular, TLR4, the cellular LPS receptor, plays an important role in the innate i��une res�onse to bacterial translocation. Selective intestinal decontamination with antibiotics have shown to reduce plasma endotoxin levels and prevents liver injury in ani�al �odels of ALD [31,32,22] . Moreover, mice deficient in CD14, the cellular co-receptor for LPS, are also resistant to alcohol�induced liver injury [17�] .…”
Section: Bacterial Translocation and Alcoholic Liver Diseasementioning
confidence: 99%
“…14, 15 In animal models, both sensitization and tolerance of Kupffer cells has been described and alcohol related liver disease can be reduced by suppression of microbial burden with antibiotics or inhibition of effector cytokines such as TNFα. 15 Recently, it was shown that TLR4 activation by LPS upregulates chemokine secretion and sensitizes stellate cells to transforming growth factor β and the activating effects of Kupffer cells. 16 Microbial translocation has also been implicated in liver disease associated with other enteric processes, such as graft versus host disease and celiac sprue.…”
Section: Introductionmentioning
confidence: 99%